PENGARUH MODEL GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN MEMECAHKAN SOAL CERITA MATERI PENYAJIAN DATA KELAS III SDN DEMANGAN 2 BANGKALAN - Ummu Hani`, Roukhil; Wulandari, Rika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine whether the Guided Discovery Learning model has a significant effect on students' ability to solve word problems on the topic of data presentation. This study employed a quantitative approach using a quasi-experimental research design. The research was conducted at SDN Demangan 2 Bangkalan. The sampling technique used was non-probability sampling. The samples consisted of all students in Class III A (34 students) as the control group and Class III B (32 students) as the experimental group. The research instruments included a test instrument in the form of essay questions and non-test instruments consisting of observation sheets and student questionnaires. Data analysis was conducted using the Shapiro–Wilk test to examine data normality, a homogeneity of variance test to assess data homogeneity, and a significance test to test the research hypothesis. The results showed that the post-test t-value (3.971) was greater than the t-table value (1.998), with a Sig. (2-tailed) value of 0.000 < 0.05. Therefore, H₀ was rejected and H₁ was accepted. It can be concluded that the Guided Discovery Learning model has a significant effect on the ability of third-grade students at SDN Demangan 2 Bangkalan to solve word problems on the topic of data presentation.